2015
DOI: 10.20884/1.anprod.2015.17.1.478
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Dried Matter, Crude Protein and Crude Fiber on Lowland Tidal Grass Fermented by Probiotic Microorganisms for Use Bali Cattle Feed

Abstract: Abstract. This study was aimed to determine nutritional value of lowland tidal grass fermented by probiotic microorganisms. This study used a completely randomized design and investigated two factors, namely varieties of lowland tidal grass (kumpai tembaga (Ischaemum rugosum), kumpai minyak (Hymenachne amplexicaulis) and kumpai padi (Oryza rufipogon)) and probiotic microorganism concentration (0.3, 0.5, 0.7 and 0.9 percent). The following parameters were observed, including dried matter content, crude protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Fiber contents reported by Kleden et al (2015) were higher than the results reported by Ahmed et al (2013) with a fiber content of 29.32% in D. aegyptium plants. A previous study showed that fermented I. rugosum, H. amplexicaulis, and O. rufipogon had fiber contents of 29.27, 29.57, and 33.07%, respectively (Muhakka et al 2015).…”
Section: Fiber Contentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Fiber contents reported by Kleden et al (2015) were higher than the results reported by Ahmed et al (2013) with a fiber content of 29.32% in D. aegyptium plants. A previous study showed that fermented I. rugosum, H. amplexicaulis, and O. rufipogon had fiber contents of 29.27, 29.57, and 33.07%, respectively (Muhakka et al 2015).…”
Section: Fiber Contentsmentioning
confidence: 97%
“…In the previous study, some swamp grasses, including H. amplexicaulis (Rostini et al 2014;Muhakka et al 2015), I. rugosum and L. hexandra (Ali et al 2012) were identified. However, more swamp vegetation has not been identified.…”
Section: Introductionmentioning
confidence: 95%
“…Peningkatan rasio konsentrat pada silase pakan komplit sangat mempengaruhi penurunan serat kasar disebabkan oleh beberapa faktor antara lain a) kandungan serat yang lebih randah dalam konsentrat; b) perubahan kondisi asam selama ensilasse yang menyebabkan terjadinya pelepasan ikatan anatar selulosa dan lignin dan hemiselulosa dan lignin; c) terjadinya penguraian serat seperti selulosa selama proses fermentasi karena aktivitas mikroorganisme selulotik dari starter yang digunakan sebagai penghasil enzim selulase yang memisah ikatan lignoselulosa dalam silase pakan komplit. Dalam proses fermentasi, mikroba akan menghasilkan enzim selulase yang mampu mengurai serat (Muhakka et al, 2015). Hal yang sama dilaporkan oleh Yanuarianto et al, (2020) bahwa menurunnya kadar SK dikarenakan fermentasi menghasilkan bakteri asam laktat yang merupakan golongan bakteri selulolitik.…”
Section: Pengaruh Perlakuan Terhadap Kadar Skunclassified
“…Venkataramanan et al (2015d) stated that the whole carrot top had crude fiber 150 g. The higher microbial activity in silage fermentation will more decrease crude fiber content. During ensilage, lignocellulose enzymes will produce microbes that degrade fibers (Muhakka et al, 2015).…”
Section: Different Inoculum Lactic Acid Bacteria Of Crude Fiber (Cf)mentioning
confidence: 99%